ALTERNATIVE ENERGY THE ROLE OF DUAL EDUCATION IN THE TRAINING OF TECHNICAL PERSONNEL - Kodirov Ismail Norkobilovich (Web of Journals Publishing, 2024)
The role of dual education, features, advantages and disadvantages of dual education in the training of qualified engineer-technical personnel in the field of alternative energy are considered. The dual education system is a flexible and effective mechanism that enables the training of highly qualified specialists required in the activities of modern production enterprises.
Keywords: production enterprises, dual education, effective and flexible mechanism, dual education system, theoretical and practical parts of the program, advantages and disadvantages of dual education.